Christianity, cults & religions ([Torrance, Calif.] : Rose Publishing, 1994)
"This presentation will allow you to compare beliefs of one religious group with Christian beliefs..."-from container
Cults/world religions: Biblical Christianity, Mormonism, Jehovah's Witnesses, Armstrongism, Unification Church, Christian Science, Unity School of Christianity, Spiritism, Church of Scientology, New Age Movement, Judaism, Hinduism, Hare Krishna, Transcendental Meditation, Buddhism, Nichiren Shoshu Buddhism, Islam, Bahai World Faith.
Keywords: International Society for Krishna Consciousness; Unity School of Christianity; Christianity and other religions; Christian sects; Latter Day Saint churches; Jehovah's Witnesses; Unification Church; Christian Science; Scientology; New Age movement; Judaism; Hinduism; Transcendental Meditation; Buddhism; Bahai Faith; Islam